Sudan : Article IV Consultation; Staff Report; Debt Sustainability Analysis; Staff Statement; Public Information Notice on the Executive Board Discussion; Statement by the Executive Director. (IMF Staff Country Reports; Country Report ;, 2010)
Sudan has been adversely affected by the global crisis through a sharp decline in oil receipts. Executive Directors welcomed the Staff-Monitored Program (SMP), which aimed to reduce the fiscal deficit, tighten monetary stance, and increase exchange rate flexibility. Directors urged the authorities to maintain prudent macroeconomic policies and to accelerate fiscal and financial sectors as well as structural reforms. Directors agreed that progress on debt relief under HIPC for Sudan is essential to remove the debt overhang and regain access to concessional financing for development and social projects.